The reality of administrative creativity among supervisors of leisure activities in sports clubs in Medina - Basalama, Abdullah Ben Omer (Journal of Physical Education, 2022)
The research aims to study the reality of administrative creativity among supervisors of leisure activities in sports clubs in Madinah. The research sample was chosen by the intentional method, where the basic research sample amounted to (50) individuals with a rate of 65.78% among the supervisors of leisure activities for leisure in sports clubs in Madinah from the research community. What the researcher found is that the supervisors of recreational activities have new ideas at work that help them to take advantage of the time available to achieve the goals. The supervisors of recreational activities have skills and abilities that enable them to persuade others when dealing with them. It is somewhat difficult to deal with difficult problems for long periods, Benefiting from the suggestions of others came in the responses of the research sample, where the axis of flexibility came in the first place within the axes of administrative creativity, a necessity and a necessity In order to develop future plans for training and developing the performance of officials of recreational activities, the administration should support the encouragement of creative ideas and reward them financially and morally to improve and develop performance, attract creative supervisors of recreational activities to work in clubs in sports institutions and feed the various departments with these creators.